Effectiveness of a therapeutic multiple-lifestyle intervention taking into account the periconceptional environment in the management of infertile couples: study design of a randomized controlled trial - the PEPCI study - Charlotte Dupont; Philippe Aegerter; Aude-Marie Foucaut; Aymeric Reyre; François J. Lhuissier; Marie Bourgain; Nathalie Chabbert-Buffet; Isabelle Cédrin-Durnerin; Lise Selleret; Emmanuel Cosson; Rachel Lévy (BMC, 2020)
Abstract Background Infertility is defined as the inability to conceive after 12 months of unprotected intercourse. It affects approximately one in six couples seeking pregnancy in France or western countries. Many lifestyle factors of the couples' pre and peri-conceptional environment (weight, diet, alcohol, tobacco, coffee, drugs, physical activity, stress, sleep...) have been identified as risk factors for infertility in both males and females. The high prevalence rates of unhealthy diets and lifestyles in the reproductive population of industrialized countries are worrisome. Nevertheless, adoption of a healthy lifestyle may improve fertility but lifestyle changes are difficult to achieve and to maintain due notably to behavioral factors. Methods Consequently, we decided to propose an interventional study aimed at improving the quality of life of infertile couples before the start of assisted reproductive technology treatment. It is a randomized controlled multicentre trial. Both members of the couples are involved in an integrated global care program (PEPCI for "Parcours Environnement PériConceptionnel en Infertilité") vs. usual care. This global intervention not only considers diet and/or physical activity but follows a holistic approach, including a multidisciplinary assessment to address complete physical, psychological and social well-being. According to patient needs, this includes interventions on weight, exercise, diet, alcohol and drugs, mental and social health. Discussion The main objective of trial is to demonstrate that periconceptional multidisciplinary care has a positive impact on reproductive functions. We will also focus on feasibility, acceptance, compliance and conditions of success of a multifaceted lifestyle intervention. Trial registration The trial was registered at ClinicalTrials.gov , Identifier: NCT02961907 on November 11, 2016.